COMPARATIVE ANALYSIS OF THE COMMON-SENSE MODEL AND BURDEN OF TREATMENT THEORY - Onawo, Hussaini Yusuf (African Journal of Social and Behavioural Sciences, 2025)
This narrative review examines two theoretical frameworks in health psychology: the Common-Sense Model of Illness Representation (CSM) and the Burden of Treatment Theory (BOTT). Through systematic thematic analysis, this review explores how these models clarify patients’ perceptions of illness and the practical demands of healthcare management. The CSM describes cognitive and emotional processes that shape understanding of illness, whereas BOTT addresses the cumulative workload patients face when managing chronic conditions. This review critically assesses the strengths, applications, weaknesses, and criticisms of both theories, highlighting points of convergence and divergence. Findings suggest that integrating CSM and BOTT provides a comprehensive framework for understanding patient experiences, particularly in the management of chronic illnesses such as diabetes. The review concludes that combining these frameworks can inform patient-centred interventions that address both cognitive perceptions and practical treatment burdens, ultimately enhancing adherence and health outcomes.